2021
DOI: 10.1021/acs.macromol.0c02744
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Structural Consequences of Associative Dynamic Cross-Linking in Acrylic Diblock Copolymers

Abstract: The composition of low-T g n-butylacrylate-block-(acetoxyaceto)ethyl acrylate block polymers is investigated as a strategy to tune the properties of dynamically cross-linked vinylogous urethane vitrimers. As the proportion of the cross-linkable block is increased, the thermorheological properties, structure, and stress relaxation evolve in ways that cannot be explained by increasing cross-link density alone. Evidence is presented that network connectivity defects such as loops and dangling ends are increased b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 96 publications
(185 reference statements)
2
56
0
Order By: Relevance
“…For practical application, versatile tuning methods of bond exchange properties are required. To date, various tuning methods have been reported while focusing on the kinds and concentration of the catalysts for the exchange reaction, cross-link density, fraction of the reactive functional groups, , and polarity of component polymers. , Additionally, it was recently revealed that the aggregation of exchangeable units greatly affected the bond exchange rate. , For example, Leibler et al reported a self-assembled nanostructure in the vitrimer network using graft-like polymers . In this design, polyethylene chains were linked by relatively long cross-linker molecules, such as dioxaborolane maleimide that had a repulsive interaction with the polyethylene, where the cross-links were exchanged via dioxaborolane metathesis.…”
Section: Introductionmentioning
confidence: 99%
“…For practical application, versatile tuning methods of bond exchange properties are required. To date, various tuning methods have been reported while focusing on the kinds and concentration of the catalysts for the exchange reaction, cross-link density, fraction of the reactive functional groups, , and polarity of component polymers. , Additionally, it was recently revealed that the aggregation of exchangeable units greatly affected the bond exchange rate. , For example, Leibler et al reported a self-assembled nanostructure in the vitrimer network using graft-like polymers . In this design, polyethylene chains were linked by relatively long cross-linker molecules, such as dioxaborolane maleimide that had a repulsive interaction with the polyethylene, where the cross-links were exchanged via dioxaborolane metathesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, VU exchange has been introduced into acrylic based copolymers based on radical polymerisation with acetoacetates as a pendent part of the copolymer, [57][58][59] as well as into acrylate based networks with a focus on supramolecular interactions based on additional Zn 2+ ions, 60 or as curing agent into epoxy-based polymer networks. 42 Interest in combining VU exchange chemistry in a straightforward way with an aza-Michael based network formation was thus the next logical step in the further development of VU dynamic materials, as the facile introduction of dynamic bonds in acrylate-based materials potentially extends the possibility of future applications into the realm of re-processable composites or reversible adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Ever since its introduction, the VU vitrimer chemistry has been picked up by several other research groups, also industrial ones, in view of its straightforward implementation in many polymer matrices and their intrinsic diversity. ,, However, a principal technical bottleneck in the application of this chemistry is its polycondensation nature, often giving rise to defects in cured VU networks, due to the release of water and formation of bubbles in freshly cured samples, generating porosity throughout the material. This porosity can be avoided by prepolymerization approaches, or it can also be generally erased by using an additional processing step, e.g., consisting of compression molding …”
Section: Introductionmentioning
confidence: 99%